2020
DOI: 10.3390/nu12020370
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Cholecalciferol Supplementation on Vitamin D Status Among a Diverse Population of Collegiate Basketball Athletes: A Quasi-Experimental Trial

Abstract: Vitamin D may play a role in performance and injury risk, yet the required supplementation dosage for collegiate athletes is unclear. The objective of this study was to define the dosage of vitamin D3 supplementation required to beneficially affect serum 25-hydroxyvitamin D (25(OH)D) among a sample of collegiate basketball athletes. This was a quasi-experimental trial, participants were allocated to one of three groups of vitamin D3 daily at the beginning of pre-season training and dependent upon their baselin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(28 citation statements)
references
References 35 publications
1
27
0
Order By: Relevance
“…A vitamin D supplementation study was conducted on 10 male and 10 female collegiate basketball players [106]. Five with mean baseline 25(OH)D concentration of 36 ± 6 ng/mL took 5000 IU/day of vitamin D 3 , whereas 13-11 of whom were African American, with mean baseline of 23 ± 3 ng/mL-took 10,000 IU/day.…”
Section: Observational Studies Of 25(oh)d Concentrations In Athletesmentioning
confidence: 99%
“…A vitamin D supplementation study was conducted on 10 male and 10 female collegiate basketball players [106]. Five with mean baseline 25(OH)D concentration of 36 ± 6 ng/mL took 5000 IU/day of vitamin D 3 , whereas 13-11 of whom were African American, with mean baseline of 23 ± 3 ng/mL-took 10,000 IU/day.…”
Section: Observational Studies Of 25(oh)d Concentrations In Athletesmentioning
confidence: 99%
“…Fat mass changes, in our cohort, were positively associated with serum 25-OH vitamin D levels, so that increased fat mass augmented circulating vitamin D levels both pre-and post-intervention. Previous studies performed on basketball players [20], athletes [7], and non-athletes [21] demonstrated a tendency towards a negative relationship between 25-OH vitamin D and fat mass. Accordingly, it is widely thought that adipose tissue sequesters vitamin D, with an impaired release of vitamin D in obese individuals compared with normal weight controls [22].…”
Section: Discussionmentioning
confidence: 84%
“…However, we hope these data can launch future investigations involving larger cohorts of competitive athletes which are historically di cult to study. To justify our small cohort, it is important to note that the number of basketball players per team remain limited (10-15/team), with small cohort numbers representative of the sport in general [1,20,24]. Additionally, we acknowledge that higher dosages of vitamin D (>4000IU/day) have been suggested to promote ergogenic bene ts, [1] especially in athletes who are de cient.…”
Section: Discussionmentioning
confidence: 99%
“…An intensified dosage of VIT E boosted to 600 mg and in combination with 1000 mg VIT C, and 8 mg beta-carotene over 32 days, ameliorate oxidative stress and therefore improving recovery markers (testosterone/cortisol, LDH), in professional basketball players during daily training [ 77 ]. Regarding VIT D, the effects of cholecalciferol supplementation on VIT D status was studied by Sekel et al [ 41 ] in a mixed sample of female and basketball players. Neither 5000 IU/day nor 10,000 IU/day show significant improvements on recovery markers (25 OH D status); however, a larger dosage (10,000 IU/day) was reported to have protective effects.…”
Section: Resultsmentioning
confidence: 99%
“…However, the formulation of this beverage varies from 7.2% sugar, 0.8% maltodextrins, and 510 mg/L Na to 6% CHO and 18.0 mM of Na among studies [ 35 , 36 , 37 ]. Regarding vitamins (VIT) or multivitamins, athletes are really keen to consume them under the premise that they would improve their health and enhance performance or recovery [ 38 , 39 , 40 ], but interventions confirming this theory are nevertheless scarce, with only one carried out with a strong scientific evidence such is VIT D [ 41 ]. Finally, a very popular ergo-nutritional aid is caffeine (CAF).…”
Section: Introductionmentioning
confidence: 99%